MANAGEMENT OF ROOT KNOT NEMATODE MELIODGYNE INCOGNITA ON HIBUSCUS ESCULENTUS (L.) BY LEAF EXTRACT OF LEUCAENA LEUCOCEPHALA (LAM.) - EDWARD, D. SAMSON; VAITHEESWARAN, M.; JEYASELVAM, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The impact of nematode pathogensis is reflected at tissue level with low sugar, starch and increased proteins, phenols and lipids. The redox enzyme activities showed a specific increase of dehydrogenase activities in the infected host plant. Varied concentrations of leaf extract treatment improved the bio-chemical profiles of nematode infected plants. The treatment of the infected plant with leaf extracts also improved environmental resistance and lowered the nematode population build up.